2022
DOI: 10.1101/2022.04.13.488264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic surveillance unfolds the dynamics of SARS-CoV-2 transmission and divergence in Bangladesh over the past two years

Abstract: The highly pathogenic virus SARS-CoV-2 has shattered the healthcare system of the world causing the COVID-19 pandemic since first detected in Wuhan, China. Therefore, scrutinizing the genome structure and tracing the transmission of the virus has gained enormous interest in designing appropriate intervention strategies to control the pandemic. In this report, we examined 4622 sequences from Bangladesh and found that they belonged to thirty-five major PANGO lineages, while Delta alone accounted for 39%, and 78%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Previous studies during the year 2020 have identified ORF10 to be under strong positive selection, along with ORF3a, ORF8 and N also depicting much higher number of dN (83)(84)(85).…”
Section: Increase In Selection Pressure On E S and Nsp1 Post-vaccinationmentioning
confidence: 91%
“…Previous studies during the year 2020 have identified ORF10 to be under strong positive selection, along with ORF3a, ORF8 and N also depicting much higher number of dN (83)(84)(85).…”
Section: Increase In Selection Pressure On E S and Nsp1 Post-vaccinationmentioning
confidence: 91%